Developing PROteolysis TArgeting Chimeras (PROTACs) for hematologic malignancies. (28th September 2022) - Wu, Yangping; Zhang, Jingliao; Zhu, Xiaofan; Zhang, Yingchi
Abstract: PROteolysis TArgeting Chimeras (PROTACs) degrade target proteins via the ubiquitin-proteasome system, providing novel insights into drug development for hematologic malignancies. PROTACs outperform conventional therapeutics and currently available small molecule inhibitors in terms of efficacy, tissue-and cell-selectivity, and side effect profile. Most importantly, PROTACs are a powerful tool for addressing "undruggable" oncogenic proteins. Despite their numerous benefits, PROTACs as therapeutics face many challenges not only in the design and synthesis but also in the evaluation of anticancer effects and clinical application. In this article, we focus on PROTACs that have demonstrated preclinical efficacy and clinical potential in the treatment of various hematologic malignancies in the last 5 years. We start with a brief overview of the functioning mechanism and major breakthroughs in this field. To provide a balanced perspective on PROTACs, we discuss the pros and cons of exploiting PROTACs for therapeutic purposes. Following that, we brainstorm ideas to optimize PROTACs for clinical application. More PROTACs will enter clinical trials soon, benefiting patients with hematologic malignancies. Highlights: PROTACs promisingly drug the "undruggable" in cancer with high selectivity. Inherent drawbacks with blurry "sweet spot" challenge PROTACs' bioavailability. Alternative exploration is much needed prior to PROTACs' clinical application.